KALIGRAFI DALAM ESTETIKA ISLAM MENURUT ISMA'IL RAJIAL-FARUQI - Dian Permatasari (UIN Sunan Kalijaga Yogyakarta, 2015)
The calligraphy is an aesthetic expression in Islamic world. Different from another arts activities that some times created controversies, such as the art of sculpture or the art of' living pictures', the existence of caligraphy is regarded as one of sacred arts that 'closely related' to al-Qur'an. According to Ismail Raji al-Faruqi, explained in this article, the calligraphy in Islamic world is not only have the artistic values but also have the theological values. For Faruqi, the art is an expression oftauhid. In this position, tauhid could be explain as the essence of aesthetic and the aesthetic is an expression of tauhid This article stated that tauhid does not confront the art's creativities and does not also face up to the aesthetics audiences.